Reflekterende skriving som kroppslig erfaring. Erfaringer fra kommunikasjonsundervisning - Øien, Aud Marie (Nordisk tidsskrift for helseforskning, 2017)
The aim of the study was to explore how third year social educator students reflect in writing on challenging practice-based experiences of communication, and how they experience the writing process. Based on selected and analyzed research material of students’ texts of reflective writing and texts of comments on reflective writing, following findings emerged: I) Experiences of reflective writing included the themes a) to learn to reflect and to become conscious of lived experiences, and b) to improve reflection on connections between experienced relationships and theoretical concepts. II) Reflecting on participation in challenging relationships in specific contexts of communication: a) the relationship of a student and a service receiver with learning disabilities preparing crossing a road, and b) the relationship between a student, a colleague and a patient with stroke, ordering food in a restaurant. Use of reflective writing facilitates self-consciousness, professional reflection and action.